Transplantation of Autogenous Bone Block With an Osseointegrated Implant: Seedling Technique With Twelve-Month Follow-Up. Issue 5 (July 2018) - Kutlu, Huseyin Burak; Goyushov, Samir; Calisan, Bünyamin; Tözüm, Tolga F.
Abstract : Objective: Loss of teeth frequently results in compound horizontal and vertical alveolar bone defects. An appropriate bone structure is the key for implant placement and bony support of soft tissues. Advanced bone augmentation techniques are required for the reconstruction of these defects. This report will present a new bone block grafting technique with 12-month follow-up. Method: The seedling technique was used to augment the alveolar bone 3-dimensionally with autologous bone block and an osseointegrated implant in a 2-stage procedure. Horizontal and vertical bone loss is revealed after cone beam radiographic examination in the right maxillary lateral incisor area. Initially, the implant was placed at the right maxillary tuber area, where the bone was abundant. After 2-months healing phase, the osseointegrated implant was harvested with the surrounding bone and transplanted to the anterior region of maxilla to augment the horizontal and the vertical components of the recipient site. Transplanted implant inserted into autogenous bone block was fixed with mini plate to the adjacent native bone. Prosthetic restoration was applied 4 months after the transplantation. Results: Seven months after the first surgery, treatment of anterior bone deficiency was accomplished. The patient was fully satisfied with the function and the esthetics of the restoration. The radiological and clinical examinations at 1-year follow-up evaluation showed successful outcome of transplanted autogenous bone block without any resorption. Conclusion: This clinical report demonstrated that anterior maxillary single-tooth replacement, according to seedling concept of autogenous bone block with osseointegrated implant, is a successful and predictable treatment modality.